Thermal and mechanical properties of bamboo fiber reinforced composites - Chin, Siew Choo; Tee, Kong Fah; Tong, Foo Sheng; Ong, Huei Ruey; Jolius, Gimbun (Elsevier, 2019)
This paper presents the thermal and mechanical properties of bamboo fiber reinforced composite (BFRC) derived from Gigantochloa scortechinii. The bamboo fibers were prepared through chemical treatment by sodium hydroxide (NaOH) followed by physical milling method. The thermal characteristics of the bamboo fiber and its polymer composite were analysed using a thermogravimetric analysis and differential scanning calorimetric. The functional groups and crystallinity of the fiber were analysed with Fourier transform infrared and x-ray diffraction spectroscopy. Meanwhile, the fiber morphology was examined using a scanning electron microscope. The BFRCs with fiber volume fractions ranging from 0 % to 40 % embedded in three thermoset resins (epoxy, polyester, vinyl ester) were subjected to tensile and flexural tests and the fracture pattern was examined. The NaOH concentration of 10 % with soaking duration of 48 h was found to produce a bamboo fiber with the highest ultimate tensile and modulus strength. The tensile and flexural properties of all the BFRCs were found to be directly proportional to the fiber volume fractions. It was found that the bamboo fiber reinforced epoxy composite (BFREC) with 40 % fiber volume fraction exhibited the highest tensile and flexural strength compared to polyester and vinyl ester composites. The method of bamboo fiber composite preparation in this work may serve as a useful guide to produce a strong BFRC for external strengthening of buildings and structures.